Assessment of the relationship between sense of coherence and surgery-related oral wound healing by using a contemporary scale: a prospective cohort study - Alanur Çiftçi Şişman; Rukiye Ceren Beker; Bahar Başak Kiziltan Eliaçik (BMC Oral Health)
Abstract Background Wound healing (WH) is a complex and dynamic biological process influenced by both physiological and psychological factors. Psychological stress can negatively impact WH in both healthy individuals and those with clinical conditions. Sense of coherence (SOC) is a well-established concept used as a reliable indicator of psychosocial factors that influence overall health. This study aimed to investigate the relationship between SOC and WH following oral surgery. Methods A total of 160 healthy, nonsmoking patients (101 females, 59 males) scheduled for oral surgery were included in the study. All procedures involved mucosal incision, mucoperiosteal flap elevation, minor bone intervention, and primary closure of the wound. SOC was measured preoperatively using the 13-item SOC questionnaire (SOC-13). WH was evaluated with the Inflammatory Proliferative Remodeling (IPR) scale at 4 days, 14 days, and 6 weeks post-surgery. Postoperative pain was assessed using a visual analog scale (VAS). Data collection and analysis were conducted by two independent, blinded researchers. Results No significant relationship was found between age, sex, SOC or IPR score (p > 0.05). However, a statistically significant negative correlation was observed between SOC and postoperative VAS score (p < 0.05). Higher SOC scores were found to be associated with lower pain. Conclusions Although SOC, a measure of psychological resilience, was not directly linked to biological wound healing, higher SOC scores were statistically associated with lower postoperative pain levels. This suggests SOC may be useful in predicting patient-reported outcomes like pain perception. Further research is needed to clarify these relationships. Trial registration Retrospectively registered on 10/10/2024, Trial number NCT06635031.